Social Relation that Triggers the Use of Code-Switching in the Novel the Architecture of Love by Ika Natassa - Clara Herlina Karjo; Fairuza Alyarizky (Lingua Cultura, 2021)
The research aimed to find out the influencing factors that caused the characters and the narrator in the novel ‘The Architecture of Love’ to do code-switching and discover how the social relation between the characters and the narrator affected the use of code-switching. Novels written by bilingual authors were frequently used as objects of analysis in code-switching research. However, most research only focused on the code-switching performed by the characters in the novels. Rarely had the attention been given to the authors or the narrators of the story. A descriptive text analysis method and library research were used to analyze the dialogues and narratives found in this novel. Results show that the reasons for most of the code switch used in the dialogues and narratives are the intentions of clarifying the speech content for the interlocutors and when talking about a particular topic. The social relation of the character shows that they treat each other as friends that have equal social status. A similar relation is also found between the writer and the readers. It can be implied that the social relation between the characters does affect the use of code-switching.